PENANGANAN PENYAKIT RADANG PARU (PNEUMONIA) PADA PEDET PRA-SAPIH (ANWEANER) DI PT. GREAT GIANT LIVESTOCK, TERBANGGI BESAR, LAMPUNG TENGAH - A. Chayrunnisa; K. Maghfiroh; Y. Priabudiman (Politeknik Negeri Lampung, 2020)
Lampung Province is one of the provinces that has very good potential in developing animal husbandry businesses. This is evidenced by the fact that Lampung province is ranked second in the largest number of beef cattle population on the island of Sumatra. Handling of disease is one of the important factors in the sustainability of a business, especially in the field of animal husbandry. Health problems in pre-weaning calves apart from diarrhea are umbilical cord infections, worms and pneumonia. One of the most common treatments for the disease is the treatment of pneumonia in calves. The aim of this study was to understand the management of pneumonia in pre-weaning calves in Central Lampung. Data were collected from March to April 2020. The cause of pneumonia was influenced by several factors, namely: bacteria, viruses, and environmental factors. The symptoms that physically contracted pneumonia include; discharge from the nose, weak body condition, head that always looks down, heavy breathing followed by coughing. Handling of pneumonia calves in Central Lampung is early detection by routine health control at the susceptible calf age, namely 2-4 weeks of age so that calves identified with pneumonia can be handled quickly. Give antibiotics (enrofloxacin) and anti-inflammatory (tolfenamic acid) with repetitions every 3 days with a drug dose of 1ml / 40 kg body weight until the calf shows signs of recovery and then recovery is carried out. Â